On Upper and Lower $μ(σ_1,σ_2)$-continuous Multifunctions (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new concepts of continuous multifunctions defined from a generalized topological space into a bitopological space, called upper $μ(σ_1,σ_2)$-continuous multifunctions and lower $μ(σ_1,σ_2)$-continuous multifunctions. Furthermore, several characterizations and some properties concerning upper $μ(σ_1,σ_2)$-continuous multifunctions and lower $μ(σ_1,σ_2)$-continuous multifunctions are discussed.
Keywords: upper $μ(σ_1,σ_2)$-continuous multifunction; lower $μ(σ_1,σ_2)$-continuous multifunction